2016
DOI: 10.3109/10428194.2015.1116121
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus reactivation after withdrawal of prophylactic antiviral therapy in patients with diffuse large B cell lymphoma

Abstract: The exact incidence and severity of hepatitis B virus (HBV) reactivation after the withdrawal of prophylactic antiviral therapy (delayed HBV reactivation) is unknown. We retrospectively analyzed 107 newly diagnosed diffuse large B cell lymphoma patients with HBV infection who received chemotherapy. The median time from the cessation of antitumor therapy to the withdrawal of prophylactic antiviral therapy was 6.1 months. The incidence of delayed HBV reactivation was 21.7% in HBsAg-positive group and 0 in HBsAg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 23 publications
0
21
2
Order By: Relevance
“…The results of previous studies regarding the effect of age on reactivation seem to be controversial. While some reported that age was not to be associated with reactivation, 5,9,26,29,30 one study reported a higher risk, 15 and another reported a lower risk. 31 Further studies are therefore needed.…”
Section: Discussionmentioning
confidence: 96%
“…The results of previous studies regarding the effect of age on reactivation seem to be controversial. While some reported that age was not to be associated with reactivation, 5,9,26,29,30 one study reported a higher risk, 15 and another reported a lower risk. 31 Further studies are therefore needed.…”
Section: Discussionmentioning
confidence: 96%
“…The most commonly studied and recommended duration of prophylactic antiviral therapy is 6‐12 months after discontinuation of anticancer therapy or immunosuppression. Reactivation beyond 12 months has been reported, so further monitoring should be considered, particularly for patients who received anti‐CD20 antibody therapy . Much less is known about the optimal duration of prophylaxis in patients receiving chronic immunosuppression, for example, transplantation and biological therapy …”
Section: Management Of Chronic Hbv In Special Populationsmentioning
confidence: 99%
“…Reactivation beyond 12 months has been reported, so further monitoring should be considered, particularly for patients who received anti-CD20 antibody therapy. (208)(209)(210) Much less is known about the optimal duration of prophylaxis in patients receiving chronic immunosuppression, for example, transplantation and biological therapy. (182,(211)(212)(213)(214) Guidance Statements for Patients Undergoing Immunosuppressive and Cytotoxic Therapy 1.…”
Section: D4 Preferred Antivirals and Duration Of Therapymentioning
confidence: 99%
“…98,[107][108][109] The antiviral prophylaxis is recommended to be administered 6 to 12 months after discontinuation of immunosuppression, 107 as HBV reactivation beyond 12 months reported, particularly in patients who received rituximab (anti-CD20 antibody). [110][111][112]…”
Section: Statementmentioning
confidence: 99%